Ctrl C + Ctrl V: Plagiarism and Knowledge on Referencing and Citation among Pre-service Teachers - Bautista, Ronalyn Maguale; Pentang, Jupeth Toriano (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
Issues on plagiarism among pre-service teachers (PSTs) have increased in modular and online learning. To confirm this, the study determined the PSTs’ level of awareness on plagiarism; their knowledge on referencing and citation; and the correlation between their level of awareness on plagiarism and knowledge on referencing and citation, with their academic performance. The study employed a descriptive-correlational research design participated by 235 PSTs randomly sampled through strata. The data were gathered through a web-based survey. Results showed that the PSTs’ level of awareness of plagiarism was moderate, while the majority have fair knowledge in referencing and citation. Also, results showed a significant relationship among the level of awareness on plagiarism, knowledge on referencing and citation, and academic performance. It is recommended that institutions equip librarians and educators to teach PSTs about citation and referencing skills. Besides, the institution should make sure that a policy is implemented to pursue academic integrity. This policy must articulate the various types of plagiarism, plagiarism measurement, and fair and consistent disciplinary actions.